Dominant formation of h-BC2N in h-BxCyNz films: CVD synthesis and characterization. (September 2021) - Seo, Tae Hoon; Lee, WonKi; Lee, Kyu Seung; Hwang, Jun Yeon; Son, Dong Ick; Ahn, Seokhoon; Cho, Hyunjin; Kim, Myung Jong
Abstract: Arranging carbon, boron, and nitrogen atoms in a sp 2 network can give rise to tunable electronic properties from insulators ( h -BN) to metals (graphene). For semiconductor applications, the construction of a ternary structure ( h -Bx Cy Nz ) is highly desirable, but its uniform and large-area synthesis has remained a great challenge. This challenge has been attempted by a facile chemical vapor deposition method with a single molecular precursor, N-tri-methyl borazine where boron, carbon, and nitrogen atoms are covalently bonded, onto Ni catalysts in conjunction with the quenching method after the synthesis. The atomic structure closely resembles h -BC2 N as revealed by XPS (B:C:N ∼ 1:1.8:1) and nanometer resolution EELS mapping, and the photoluminescence and electroluminescence observed from the h -BC2 N film were in agreement, proving its well-established bandgap of 2.15 eV. As a practical application, the utilization of h -BC2 N film for 2D light emitting diodes was demonstrated. Though films might have impurities such as small h -BN fragments and h -Bx Cy Nz other than h -BC2 N phase, we believe that this work provide a starting point of controlling the ternary BCN compounds that retain sp 2 hybridized chemical bonds. Graphical abstract: h-BC2N has been synthesized by a facile chemical vapor deposition method with a single molecular precursor, N-tri-methyl borazine. Image 1